2006
DOI: 10.1002/jemt.20339
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the conditions required to image live human epithelial and fibroblast cells using atomic force microscopy

Abstract: Successful imaging of living human cells using atomic force microscopy (AFM) is influenced by many variables including cell culture conditions, cell morphology, surface topography, scan parameters, and cantilever choice. In this study, these variables were investigated while imaging two morphologically distinct human cell lines, namely LL24 (fibroblasts) and NCI H727 (epithelial) cells. The cell types used in this study were found to require different parameter settings to produce images showing the greatest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…AFM imaging of live cells is complicated and requires the maintenance of physiologic conditions [20]. AFM cell imaging in air conditions is attributed to the increasing hardness of the cell by dehydration [21].…”
Section: Discussionmentioning
confidence: 99%
“…AFM imaging of live cells is complicated and requires the maintenance of physiologic conditions [20]. AFM cell imaging in air conditions is attributed to the increasing hardness of the cell by dehydration [21].…”
Section: Discussionmentioning
confidence: 99%
“…A critical first step has been to develop a new technology that integrates AFM with TIRF (total internal reflection fluorescence) and FSD (fast-spinning disc) confocal microscopy to investigate cellular behaviour at the subcellular level, thus providing high spatial and temporal resolution (Trache and Lim, 2009). Other necessary considerations for application development include the selection of cantilever tips with spring constants that are appropriate to the cell type under analysis, as well as scanning parameters such as the resonant frequency employed (Murphy et al, 2006). The flexibility of the AFM and its combination with light microscopy techniques, namely DIC (differential interference contrast microscopy) and CLSM, have allowed the organization of adhesion molecules on the surface and their correlation with structures involved in binding to be elucidated (Poole et al, 2004).…”
Section: Hybrid Instrumentationmentioning
confidence: 99%
“…Murphy M.F. et al reported that successful imaging of live human cells using AFM was influenced by many variables including cell culture conditions, cell morphology, surface topography, scan parameters and cantilever choice [2]. Lee et al successfully observed the angiotensin II (Ang II) induced changes in fixed and live mesangial cell by AFM [3].…”
Section: Introductionmentioning
confidence: 98%